Familial amyotrophic lateral sclerosis with a point mutation of SOD-1: intrafamilial heterogeneity of disease duration associated with neurofibrillary tangles. Issue 3 (September 1995) - Orrell, R W; King, A W; Hilton, D A; Campbell, M J; Lane, R J; de Belleroche, J S
Abstract : Mutations of SOD-1 have recently been associated with autosomal dominant familial amyotrophic lateral sclerosis (ALS). A patient is described with a 20 year duration of motor neuron disease, with clinical features of ALS, who was heterozygous for a point mutation ATT to ACT leading to substitution of isoleucine for threonine at codon 113 in exon 4 of SOD-1. This mutation has previously been described in two families with ALS and three apparently sporadic cases of ALS. The patient described here had a family history suggestive of autosomal dominant inheritance of this genetic mutation; other members of the family having a more typical disease duration. Unusual pathological features included neurofibrillary tangles in neurons of the globus pallidus, substantia nigra, locus coeruleus, and inferior olivary nuclei, and absence of ubiquitin immunoreactive inclusions in motor neurons. This may reflect the slow progression of the neurodegeneration associated with the SOD-1 mutation in this patient. The prolonged survival, of over 20 years, with other family members having a more typical survival of two to three years, has important implications for genetic counselling in families with ALS in addition to the fundamental biological questions concerning the influence of these mutations on disease expression.